2018
DOI: 10.1177/0022167818785070
|View full text |Cite
|
Sign up to set email alerts
|

Representations of Hope, Goals, and Meaning From Lay Person’s Perspectives in Two African Contexts

Abstract: In the rapidly expanding field of positive psychology, a core question is now what the relationships among various positive constructs are and how we can understand this in various contexts. We aimed to explore the possible nomological network linking the constructs hope, goals, and meaning from a bottom-up Africentric perspective in two African contexts (Ghana and South Africa) among samples of 18 emerging adults between the ages of 18 and 25 years in each context. Connotations of hope, goals, and meaning as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 48 publications
2
8
0
Order By: Relevance
“…The importance of these resources has been discussed extensively in resilience research (Botha & van den Berg, 2016 ; Collishaw et al, 2016 ; Haffejee & Theron, 2019 ; Mosavel et al, 2015 ; Van Breda, 2018 ). Reliance on faith and religious beliefs is also consistent with existing research in contexts challenged by multiple adversities (Abualkibash & Lera, 2015 ; Panter‐Brick & Eggerman, 2012 ; Wilson et al, 2016 ). Knowing what helps children to adapt provides opportunities to develop contextually and developmentally relevant interventions and support systems to enhance diverse resilience.…”
Section: Discussion and Recommendationssupporting
confidence: 82%
“…The importance of these resources has been discussed extensively in resilience research (Botha & van den Berg, 2016 ; Collishaw et al, 2016 ; Haffejee & Theron, 2019 ; Mosavel et al, 2015 ; Van Breda, 2018 ). Reliance on faith and religious beliefs is also consistent with existing research in contexts challenged by multiple adversities (Abualkibash & Lera, 2015 ; Panter‐Brick & Eggerman, 2012 ; Wilson et al, 2016 ). Knowing what helps children to adapt provides opportunities to develop contextually and developmentally relevant interventions and support systems to enhance diverse resilience.…”
Section: Discussion and Recommendationssupporting
confidence: 82%
“…The ways participants described faith and agency were consistent with the psychology of radical hope conceptual framework (Mosley et al, 2020) and existing research. Participants mentioned spirituality as an expression of hope (i.e., faith), which is consistent with theories of personal hope in the United States (e.g., Scioli et al, 2011) and qualitative findings in African countries (Wilson et al, 2021). However, participants’ articulation of faith and radical hope was not limited to spirituality.…”
Section: Discussionsupporting
confidence: 78%
“…For example, Bernardo (2010) found that Filipino college students showed an external locus of hope (i.e., agency toward the future coming from family, peers, and spiritual beings). In addition, Wilson et al (2021) found that hope was strongly tied to collective identity and Afrocentric worldviews (i.e., communalism, collectivism, spirituality) among South African and Ghanaian adults. This notion that factors outside of the individual contributes to a sense of hope aligns with collectivist values, or a “social way of being, oriented toward in-groups and away from out-groups” (Oyserman et al, 2002, p. 5) and includes a sense of interdependence (Brewer & Chen, 2007).…”
Section: Overview Of Psychology Models Of Traditional Hopementioning
confidence: 99%
“…However, the question of what is valuable or what makes a good life , has long generated various answers from scholars across disciplines (Bauer et al, 2005; Forgas & Baumeister, 2018; Wong, 2011). While the majority of the so-called universal human values have emerged from, and informed by, Western-individualistic cultural orientation and values (Kostina et al, 2015; Schwartz, 2007), empirical research emanating from the more collectivistic, non-Western sociocultural perspectives (e.g., East Asian and Africa) have revealed different set of values and what individuals conceive as the good life (Kim et al, 2018; Uchida & Ogihara, 2012; Wilson et al, 2021). These emerging findings essentially suggest that a significant number of cognitive and epistemic values, previously considered as universal, are not necessarily valued in all contexts.…”
Section: Introductionmentioning
confidence: 99%
“…The literature is replete with case reports across Africa that describe and examine what the African people consider as valuable—which, fundamentally, should form the basis for strengths-based and positive interventions (Renner et al, 2003; Wilson et al, 2021; Wilson Fadiji et al, 2021; Wissing, 2013). Citing proverbs and maxims, Gyekye discusses several shared values amongst the Akan people of Ghana, most of which are also observed across many countries in sub-Saharan Africa: peace, happiness or satisfaction (human flourishing), justice, dignity, respect, equality, freedom, and security (Gyekye, 1996; 2011).…”
Section: Introductionmentioning
confidence: 99%